Analisis Sistem dan Prosedur Pemberian Kredit pada LPD Desa Pakraman Keramas - Yasa, Ni Made Uliasari; Yuniarta, Gede Adi (Universitas Pendidikan Ganesha, 2022)
The purpose of this research is to find out how the system and procedure for granting credit at the LPD of Pakraman Keramas Village. The data used in this research is qualitative data which is supported by credit forms, credit analysis, main tasks and organizational structure. The subject of this research is the LPD of Pakraman Keramas Village and the object is the system and procedure for granting credit at the LPD of Pakraman Keramas Village. Data collection techniques are observation, interviews, documentation. The data and the data obtained will be analyzed using qualitative descriptive analysis. The results of this research become to the system and procedures for providing credit are adequate and good. In the process of granting credit to the LPD of Pakraman Keramas Village, it will involve several parts, namely the credit department, village administrators, head of the LPD, Cashier Section and General/Administrative Section. The debtor submits an application for credit, the credit department will examine the guarantee, the credit application and the head of the LPD will provide credit decisions. And for the cashier who will make receipts and will carry out credit realization, and for the credit department which will archive all documents from debtors of regional levies.